2013
DOI: 10.21161/mjm.44312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiogram profile and cross transmission of Pseudomonas aeruginosa in a tertiary burn unit

Abstract: Aims:Pseudomonas aeruginosa is an opportunistic pathogen that still develops life threatening infections in patients with immunological system defects like burns. The major problem with this organism is the ability to persist during infections due to its high rate of resistance to many drugs. This study was designed to evaluate the prevalence and drug susceptibility profile of Pseudomonas aeruginosa in patients admitted to a burn unit in a tertiary health facility. Methodology and Result: From 80 selected pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 2 publications
1
4
1
Order By: Relevance
“…In contrast, the 33% MDR P . aeruginosa isolation rate from this study is lower than the findings from other studies elsewhere, which reported from as low as 40.7% to as high as 100% [ 8 , 9 , 27 , 33 , 39 ]. The possible explanation for such disparity might be differences in the study population, use of different antibiotic regimes, extensive use of the antimicrobial drugs studied in those settings, persistent presence of resistant strains in hospitals, cross-contamination from the laboratory environments during culturing or the quality of hygiene in the hospital environments under study.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In contrast, the 33% MDR P . aeruginosa isolation rate from this study is lower than the findings from other studies elsewhere, which reported from as low as 40.7% to as high as 100% [ 8 , 9 , 27 , 33 , 39 ]. The possible explanation for such disparity might be differences in the study population, use of different antibiotic regimes, extensive use of the antimicrobial drugs studied in those settings, persistent presence of resistant strains in hospitals, cross-contamination from the laboratory environments during culturing or the quality of hygiene in the hospital environments under study.…”
Section: Discussioncontrasting
confidence: 84%
“…The same low rate of resistance (about 11%) against Amikacin was also documented in other studies including Yemen [ 33 ], Ghana [ 32 ], Kenya [ 25 ], and South Africa [ 20 ]. However, much higher resistance rates were reported from elsewhere for Amikacin: 21% in Turkey [ 23 ], 32.1% in Nigeria [ 8 ], 48.1% in Iraq [ 31 ], 50% in Malaysia [ 19 ], 73.2% in India [ 9 ], 75% in Pakistan [ 30 ], and 89.4% in Iran [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations